Enfoques pedagógicos de la topografía incorporada: un taller que desentraña los paisajes ocultos e imaginarios de Elaionas - Marda, Nelly; Kakalis, Christos; Ioannou, Olga (ZARCH, 2017)
A workshop aiming to activate the sensory experience of individuals within the urban landscape was introduced to the students of a postgraduate course of architecture. The course seeks to explorecity complexity by mapping the urban phenomena. These readings provide the base for the creation of integral strategic interventions. In the two years it has run, students have shown a preference for analytical tools. This time however, they were asked to perform a series of exercises that sought to increase their body awareness, to help them navigate and read the landscape through their sensory perceptions. The authors of this paper contemplate on the use of mapping methodologies, embodied topography and its relation to the more hidden and imaginary landscapes of the city. They present the reader with a description of the workshop articulation, segments of the student projects and its pedagogical outcomes. KEYWORDS: .